A Traditional State: Principles of the Organization of Power and Managerial Practice in the States of the Ancient World and the Middle Ages - Lyubashits, Valentin Y.; Razuvaev, Nikolai V.; Mamychev, Alexey Yu.; Duravkin, Pavel M.; Hotsuliak, Svetlana L. (Journal of History Culture and Art Research, 2019)
This article presents an analysis of the socio-economic specifics and political and legal characteristics of a traditional state. The authors illustrate the latter on a vast array of historical examples from the evolution and development of the ancient and medieval states. The authors substantiate that the key feature of traditional states is the absence of the state apparatus in its classical political and legal interpretation. At the same time, using various historical examples, the traditional state, and its public-imperious organization has been proved to base on an extensive system of personal relations and property basis, which was legally documented and represented in the socio-political reality in the land ownership. The absence of public service and, accordingly, state-service relations in the traditional state, in our opinion, was the reason that its state apparatus was not its structural and organizational basis. It seems that this feature should be considered one of the main typological characteristics of the traditional state. In science, however, it is stated that such indivisibility of managerial and economic functions had, allegedly, a place only at the earliest stages of statehood. Gradually, as the state develops, there is a distinction between private and public law functions of the state, due, among other things, to the separation of private property of the ruler from the property of the state (treasury).